GLP-1 receptor agonist as a modulator of innate immunity - Chen, Jun; Mei, Aihua; Wei, Yingying; Li, Chunlei; Qian, Hang; Min, Xinwen; Yang, Handong; Dong, Lingli; Rao, Xiaoquan; Zhong, Jixin (Frontiers in Immunology, 2022)
Glucagon-like peptide-1 (GLP-1) is a 30-amino acid hormone secreted by L cells in the distal ileum, colon, and pancreatic α cells, which participates in blood sugar regulation by promoting insulin release, reducing glucagon levels, delaying gastric emptying, increasing satiety, and reducing appetite. GLP-1 specifically binds to the glucagon-like peptide-1 receptor (GLP-1R) in the body, directly stimulating the secretion of insulin by pancreatic β-cells, promoting proliferation and differentiation, and inhibiting cell apoptosis, thereby exerting a glycemic lowering effect. The glycemic regulating effect of GLP-1 and its analogues has been well studied in human and murine models in the circumstance of many diseases. Recent studies found that GLP-1 is able to modulate innate immune response in a number of inflammatory diseases. In the present review, we summarize the research progression of GLP-1 and its analogues in immunomodulation and related signal pathways.